2018
DOI: 10.3126/jpan.v6i2.21752
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Pattern in Psychiatric Ward in a Tertiary Care Hospital in Eastern Nepal

Abstract: Introduction: Worldwide, the morbidity of psychiatric illnesses is on the rise. Quality in-patient services are a part of quality mental health services provision. Knowledge about the pattern of illness among patients admitted to the ward could help the service providers to plan better and provide better services. This study was undertaken to explore the clinico-demographic profile of patients admitted to psychiatric ward at BPKIHS..Material And Method: This is a hospital based retrospective and cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…However, participants discharged without improvement should not be overlooked because this group of patients is at higher risk of early readmission and subsequent progression of a chronic condition. This finding is similar to studies from Ethiopia (90.3%) [ 12 ] and Nepal (92.2%) [ 15 ]. However, it’s higher than the reports of another study done in Ethiopia (74.9%) [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, participants discharged without improvement should not be overlooked because this group of patients is at higher risk of early readmission and subsequent progression of a chronic condition. This finding is similar to studies from Ethiopia (90.3%) [ 12 ] and Nepal (92.2%) [ 15 ]. However, it’s higher than the reports of another study done in Ethiopia (74.9%) [ 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Data was collected through patient interviews and a review of medical records using a questionnaire developed after reviewing relevant literature [12,[15][16][17]. For patient interviews, the questionnaire was translated into the most common local languages (Afan Oromo and Amharic).…”
Section: Data Collection Instrument and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with the study conducted in the eastern part of Nepal, which revealed the majority of the admitted patients in the psychiatric ward were in the age group of 20-59 years. 5 We have found that male subjects outnumbered female subjects by almost triple, which might be due to the existing gender bias in Nepalese society, where male problems are paid more attention by family members. This finding is in accordance with different studies from Asian countries, where the majority of the patients were male.…”
Section: Discussionmentioning
confidence: 76%